Transformation of Building and Space Management from an Administrative to a Strategic Approach: A Qualitative Study in Vocational High Schools (SMK) in Tangerang Regency - Lili Hastuti; Alifa Syauqi Hatami; Madhakomala Madhakomala (MASI Mandiri Edukasi, 2026)
The management of school buildings and learning spaces plays a critical role in supporting the quality of vocational education. However, existing studies largely emphasize administrative compliance, with limited attention to how facility management can strategically support pedagogical objectives, particularly in vocational high schools (SMK). This gap highlights the need to reconceptualize facility management as a strategic function aligned with learning outcomes. This study aims to explore the transformation of building and space management from an administrative approach to a strategic perspective in SMKs in Kabupaten Tangerang. A qualitative research design was employed, using observations, semi-structured interviews with school administrators and teachers, and document analysis. The findings indicate that although formal procedures for facility management are in place, their implementation remains predominantly administrative. Space utilization is often disconnected from instructional needs and technological integration. The study reveals limited adoption of strategic practices that align physical space with vocational learning requirements. The novelty of this research lies in its focus on repositioning educational facility management as a strategic component that directly supports skill-based learning in vocational education. The study underscores the importance of integrating space planning, technology, and pedagogy to enhance learning effectiveness and optimize resource use. These findings have practical implications for policymakers and school leaders in promoting sustainable, strategic management of educational facilities